Design for the transfer of a validated liquid chromatography/tandem mass spectrometry analytical method for the determination of antimicrobial residues in honey from low‐resolution to high‐resolution mass spectrometry. (15th June 2017) - El Hawari, Khaled; Al Iskandarani, Mohamad; Mompelat, Sophie; Hurtaud‐Pessel, Dominique; Verdon, Eric
Abstract : Rationale: This paper investigates the validity of the transfer of a liquid chromatography/tandem mass spectrometry (LC/MS/MS) method for the determination of veterinary medicinal products in honey and compares it with an LC/linear ion trap/Orbitrap mass spectrometry method. A descriptive statistical approach was used in order to assess whether such a transfer would succeed or fail. This approach is based on the simultaneous evaluation of the trueness and of the intermediate precision for each compound at a 95% interval of confidence of both analytical techniques. Methods: Two grams of honey were placed in a centrifuge tube and diluted with 2.5 mL of ultra‐pure water and 2.5 mL of acidified methanol with hydrochloric acid at 2 mol.mL –1 . The extract was purified with 50 mg of primary secondary amine and then analyzed using LC/MS/MS in multiple reaction monitoring (MRM) mode and LC/orbitrap high‐resolution mass spectrometry in full scan mode. Both analytical techniques were compared by using the descriptive statistical approach for the determination of antimicrobial residues in honey. Results: The transfer of the method showed that the Orbitrap system provides the same accurate analytical results compared with the LC/MS/MS method except for 4‐epitetracycline, anhydroerythromycin A, erythromycin A enol ether, and dihydrostreptomycin. Furthermore, the LC/LTQ‐Orbitrap system is capable of successfully competing with the LC/MS/MS method by additional provision of high mass resolution and mass accuracy even though it shows less sensitivity compared with the LC/MS/MS instrument. CCα levels for most analytes were 1.3 times higher by LC/MS/MS than those observed by LC/LTQ‐Orbitrap. The method was assessed in terms of relative bias through analysis of a reference material provided by FAPAS (Food Analysis Performance and Assessment Scheme) and also through the control of several contaminated honey samples from local Lebanese markets. Satisfactory relative bias was below 22% except for tetracycline found in one sample that showed a higher bias at 29%. Conclusions: The LC/LTQ‐Orbitrap method offers adequate performance in comparison with previously validated method on a LC/MS/MS system resulting in acceptance of the transfer of the method from LC/MS/MS to LC/LTQ‐Orbitrap. Copyright © 2017 John Wiley & Sons, Ltd.